2015
DOI: 10.1371/journal.pone.0138116
|View full text |Cite
|
Sign up to set email alerts
|

Do Interventions that Promote Awareness of Rights Increase Use of Maternity Care Services? A Systematic Review

Abstract: Twenty years after the rights of women to go through pregnancy and childbirth safely were recognized by governments, we assessed the effects of interventions that promote awareness of these rights to increase use of maternity care services. Using inclusion and exclusion criteria defined in a peer-reviewed protocol, we searched published and grey literature from one database of studies on maternal health, two search engines, an internet search and contact with experts. From the 707 unique documents found, 219 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 8 publications
2
48
0
1
Order By: Relevance
“…Marmots' review of the social determinants of health encourages the development of partnerships, with those affected by social inequities working with their health practitioners . Central to this approach is the development of a system that empowers women to have a real say in decisions that affect their lives, and that recognizes their fundamental human rights . These values are echoed in the National Institute of Clinical Excellence (NICE) guidelines for women with complex social factors, which called for a reorganization of maternity services to improve antenatal care for this population and identified gaps in evidence with respect to effective service provision.…”
Section: Introductionmentioning
confidence: 99%
“…Marmots' review of the social determinants of health encourages the development of partnerships, with those affected by social inequities working with their health practitioners . Central to this approach is the development of a system that empowers women to have a real say in decisions that affect their lives, and that recognizes their fundamental human rights . These values are echoed in the National Institute of Clinical Excellence (NICE) guidelines for women with complex social factors, which called for a reorganization of maternity services to improve antenatal care for this population and identified gaps in evidence with respect to effective service provision.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous systematic review, we assessed the effects of interventions that promote awareness of rights on the use of maternity care services in low and middle income countries (LMICs) [ 9 ]. We identified four studies promoting awareness of rights that reported health outcomes with clear research methods detailing increases in antenatal care [ 10 – 12 ] and facility births [ 11 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…One finds no evidence that reducing supervision frequency has any effect on service use. George et al (2015) find that all four included studies of interventions to promote rights awareness for maternity healthcare report increased use of health facilities (though one is not statistically significant) They also find that studies reported improvements in perceptions and observed quality of services. Willey et al's (2013) review of interventions to improve healthcare delivery finds mixed results for impact on quality of care.…”
Section: Educationmentioning
confidence: 91%
“…Three high-confidence reviews (Guerrero et al, 2012;Carr-Hill et al 2015;Snilstveit et al 2015) and one medium-confidence review (George et al 2015) assess the impact on public servant characteristics and behaviours. All three high-confidence reviews relate to education programmes.…”
Section: Public Servant Characteristics and Behaviourmentioning
confidence: 99%
See 1 more Smart Citation